Treprostinil Iontophoresis Improves Digital Blood Flow during Local Cooling in Systemic Sclerosis. (April 2016) - Gaillard‐Bigot, Florence; Roustit, Matthieu; Blaise, Sophie; Cracowski, Claire; Seinturier, Christophe; Imbert, Bernard; Carpentier, Patrick; Cracowski, Jean‐Luc
Abstract: Introduction: Severe Raynaud's syndrome and DUs are the most prevalent manifestations of SSc peripheral microvascular disease. We tested whether treprostinil iontophoresis on the finger pad of patients with SSc would improve digital blood flow during hand cooling. Methods: Eleven patients with limited cutaneous SSc underwent a double‐blinded iontophoresis of treprostinil (2.56 × 10 −4 M during two hours) and placebo (NaCl 0.9%) on two finger pads. Then, the hand was inserted for 30 minutes in a fenestrated cooling box at 8°C, and skin blood flow was recorded continuously using LSCI. Results: During the local cooling, CVC was significantly higher at the treprostinil site than at the placebo site and remained higher 30 minutes after the test. Conclusions: In patients with SSc, digital treprostinil iontophoresis shifts skin blood flow upward during local cooling of the hand and during the initial rewarming phase. Digital treprostinil iontophoresis should now be tested in larger scale studies.